KNOWLEDGE FORMATION SUPPORT SYSTEM, PARAMETER RETRIEVAL METHOD AND PROGRAM PRODUCT - IIDA TOYOO (2004)
PROBLEM TO BE SOLVED: To provide a system capable of easily retrieving and determining effective parameters for calculating effective feature value for determining normal/abnormal of examination subject in an examination device and a diagnostic device. SOLUTION: The system comprises a parameter retrieval part 15 for retrieving parameters to be used for calculating the feature value, a feature value calculation part 12 for calculating a plurality of feature amounts based on the parameters retrieved in the parameter retrieval part 15 for a given sample data (1, 2) containing a normal data and an abnormal data, and an evaluation part 13 for outputting evaluation for the parameters as an evaluation value from the calculation results obtained by the feature value calculation part. The parameter retrieval part can determine the effective feature value of high evaluation and their effective parameters at once by again retrieval based on the evaluation result of the evaluation part. COPYRIGHT: (C)2005,JPO&NCIPI